Application of different transient sorption methods to evaluate moisture diffusion coefficients of building materials on the hygroscopic range - J. M. P. Q. Delgado (2012)
Typically, moisture transport coefficients are determined either by stationary measurements,as standard cup set-up and modified cup method, or by dynamic measurements,as the means of the type ffiffit p rule in the initial phase of adsorption processes, logarithmicprocedure in the end stage of adsorption processes, the half-time method, the momentmethod, and the hybrid 1-term method.The aim of this work was to test the usability of the five dynamic calculation methodsto define the moisture diffusivity in the hygroscopic range of different building materials.The results obtained were compared in order to evaluate the discrepancies betweenthe different calculation techniques. Advantages in time saving using each experimentaltechnique were compared with the feasibility of each process.Two commonly used building materials are considered in the study, gypsum boardand gypsum plaster, for adsorptive measurement of the moisture diffusivity at threedifferent temperatures in three different relative humidity ranges.